Coronavirus disease 2019: What we know? - He, Feng (J Med Virol, 2020)
In late December 2019, a cluster of unexplained pneumonia cases has been reported in Wuhan, China. A few days later, the causative agent of this mysterious pneumonia was identified as a novel coronavirus. This causative virus has been temporarily named as severe acute respiratory syndrome coronavirus 2 and the relevant infected disease has been named as coronavirus disease 2019 (COVID‐19) by the World Health Organization, respectively. The COVID‐19 epidemic is spreading in China and all over the world now. The purpose of this review is primarily to review the pathogen, clinical features, diagnosis, and treatment of COVID‐19, but also to comment briefly on the epidemiology and pathology based on the current evidence.